Can we cope with the complexity of reality? : why craving easy answers is at the root of our problems : reflections on science, self-illusions, religion, democracy and educaiton for a viable future /: why craving easy answers is at the root of our problems : reflections on science, self-illusions, religion, democracy and educaiton for a viable future. (2020) - Jucker, Rolf, 1963-
No abstract available